On the boundedness of some classes of integral operators in weighted Lebesgue spaces - Arendarenko, Larisa; Oinarov, Ryskul; Persson, Lars-Erik (Eurasian Mathematical Journal, 2025)
Some new Hardy-type inequalities for Hardy–Volterra integral operators are proved and discussed. The case \(1 < q < p < ∞\) is considered, and the involved kernels satisfy conditions which are less restrictive than the usual Oinarov condition.